Comparison of Van Allen Probes Energetic Electron Data With Corresponding GOES‐15 Measurements: 2012–2018. Issue 12 (4th December 2019) - Baker, D. N.; Zhao, H.; Li, X.; Kanekal, S. G.; Jaynes, A. N.; Kress, B. T.; Rodriguez, J. V.; Singer, H. J.; Claudepierre, S. G.; Fennell, J. F.; Hoxie, V.
Abstract: Electron fluxes (especially at energies E > 0.8 and 2 MeV) have been measured for many years by sensors on board the Geostationary Operational Environmental Satellite (GOES). These long‐term data (nominally at L ~ 6.6) have become a mainstay for monitoring the Earth's radiation environment. We have carried out a study directly comparing the comprehensive radiation belt particle measurements from the National Aeronautics and Space Administration dual‐spacecraft Van Allen Probes (Radiation Belt Storm Probes) sensor systems with selected GOES operational data. The Van Allen Probes have measured the properties of radiation belt electrons virtually continuously from September 2012 to 2018. We make statistical comparisons of Van Allen Probes electron data near L = 6 with concurrent daily averages of equivalent GOES‐15 flux values. We also compare Van Allen Probes data at various other L values and at a much broader range of particle energies with the more limited baseline GOES‐15 values. These comparisons inform us about the relative calibrations between the scientific and operational systems and also allow us to assess how well GOES data correlate with radiation belt behavior well away from the geostationary orbit location. We find that GOES daily average flux values can be a factor of 100 (or more) below the corresponding Van Allen Probes daily averaged fluxes at L = 6.0. This is due to the fact that GOES at stationary orbit often has excursions over large ranges of L space during a given day and strong radial gradients exist in this region of the magnetosphere. These results indicate that it is crucial to augment geosynchronous GOES observations with observations in the core of the outer belt (L ≲5.0). Key Points: Comparison of operational GOES data with NASA science data Statistical study of radiation belt properties over 6 years Study shows radial range and energy range where GOES can monitor radiation belts